“KEEP YOUR EYES ON THE PRIZE”: THE BACKGROUND AND EVOLUTION OF THE PROVERB - Clay Doyle, Charles (Proverbium - Yearbook, 2017)
The proverb “Keep your eyes on the prize” achieved popularity as a motto or hortatory slogan in the American civil rights movement of the 1960s. The saying had become common as a refrain in an old spiritual—a favorite “freedom song”—replacing the traditional refrain, “Keep your hand on the plow.” Prior to its widespread use by participants in the civil rights movement, interesting analogs occurred. In the seventeenth century and throughout the nineteenth centuries, it appeared with some frequency as a Christian exhortation. In recent times “Keep your eyes on the prize” has been used more broadly to urge focused effort toward a variety of goals.